STRATEGI PENGELOLAAN LAHAN PERTANIAN UNTUK MENGURANGI DAMPAK ABU VULKANIK GUNUNGAPI BROMO, JAWA TIMUR - , Edwin Maulana, Prof. Dr.rer.nat. Junun Sartohadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to develop agricultural land management strategies to reduce the impact of volcanic ash Bromo Volcano. Volcanic ash hazard mapping of Bromo was conducted to identify areas affected by the eruption of the Bromo Volcano in 2010. Field surveys and GIS (Geographic Information System) analysis were performed to create hazard maps of volcanic ash. Land suitability assessment was conducted to determine the characteristics and land quality after the eruption of Bromo Volcano. Matching by weighting technique using AHP (Analytic Hierarchy Process) is used to determine the land suitability for agriculture. Land management strategies were analyzed by identifying areas affected by volcanic ash eruption and land characteristics analysis. The research results showed that 8665.20 hectares or 12.77% are vulnerable to the threat of volcanic ash Bromo Volcano. There are three main factors that caused the area to be very vulnerable to the hazards of volcanic ash, the wind direction, the shape of the crater of Bromo, and the elevation and location of the caldera of Sukapura. Land suitability in Tengger Mountain dominated by crops of potatoes and cabbage. The main limitation factors such as low pH and CEC (Cation Exchange Capacity), too high rainfall, as well as slope and intensive erosion. Land management strategies that can be applied is organic materials and phosphate addition to increase soil pH and CEC as well as land conservation action.